INVENTORY OF PLANT PESTS AND DISEASES IN SEI BINGAI LANGKAT DISTRICT - M. Sidik Tarigan; Desi Sri Pasca Sari Sembiring; Wasito (Yayasan Sinergi Multidimensi Kreatif, 2024)
Bitter melon, chili and corn are important commodities in Sei Binga Yuuk District. However, production of this crop is often hampered by pest and disease attacks. This research aims to identify pests and diseases that attack bitter melon, chili and corn plants in Sei Bingai District. The method used is a direct survey in the field with visual observation and sampling. It is hoped that this research will provide useful information for farmers in controlling pests and diseases of bitter melon, chili and corn plants in Sei Bingai District. Identify pests and diseases on bitter melon, chili and corn plants, namely: javelina, common brown night butterfly, grasshopper, palm grasshopper, koksi beetle, soldier beetle, seed fly, snail, leaf spot, fruit rot, leaf rust, and stem rot